Inhibitory Effect of Allyl Isothiocyanate on Clostridium perfringens and Its Application of Cooked Pork - Linying LI; Yilin LIN; Yaosheng WEN; Caihu LIAO; Yigang YU (Shipin gongye ke-ji, 2023)
The study aimed to investigate the inhibitory activity and mechanism of action of allyl isothiocyanate (AITC) against Clostridium perfringens (C. perfringens). Firstly, the inhibitory effect of AITC on C. perfringens was evaluated by determining the minimum inhibitory concentration (MIC) and plotting the growth curve. Secondly, the effect of AITC on C. perfringens cell membranes was assessed by scanning electron microscopy to observe cell morphology and by measuring cell membrane integrity with a propidium iodide staining assay. In addition, the impact of AITC on the metabolism of C. perfringens was investigated using SDS-PAGE profile and an ATPase activity assay. Finally, the inhibitory effect of AITC on C. perfringens in cooked ground pork was examined. The experimental results showed that AITC could effectively inhibit the growth of C. perfringens, and the MIC of AITC was determined to be 0.1 μL/mL. AITC was able to induce cell membrane deformations, such as rupture and depression, resulting in the loss of C. perfringens cell membrane integrity, and the degree of membrane damage increased with AITC concentration. Meanwhile, AITC could reduce the protein content and ATPase activity of C. perfringens, which had an impact on normal cellular metabolism. Furthermore, the addition of 0.1%~0.4% AITC significantly inhibited the growth of C. perfringens in cooked ground pork (P<0.05). In conclusion, AITC could achieve bacterial inhibition by disrupting the cell membrane of C. perfringens and interfering with protein metabolism, and this study offered a theoretical foundation for the use of natural bacterial inhibitors in the meat industry.